Determining the transfer length in prestressed concrete railroad ties produced in the United States - Murphy, Robert Lawrence (Kansas State University, 2012)
This thesis presents results from transfer length measurements on prestressed concrete railroad ties. Results are shown from the four main producers of concrete ties in the United States. Six prestressed concrete tie plants were visited by the research team to measure transfer length on ties with various mix designs and prestressing reinforcement. After all plants had been visited, a total of nine concrete-mix designs and 10 reinforcement variations were tested. Overall, 220 transfer length measurements were conducted on prestressed concrete railroad ties during the duration of this research project. This was the first coordinated effort to measure transfer lengths in concrete railroad ties ever conducted in the industry. Concrete strains were monitored using the standard Whittemore gage, as well as a non-contact procedure called laser-speckle imaging (LSI). This method to measure transfer lengths has been developed at Kansas State University (KSU). Ties measured using the Whittemore gage were sent back to the civil engineering structural laboratory at KSU so the long-term transfer lengths could be monitored. After a certain period of time, the ties were load-tested according to the American Railway Engineering and Maintenance-of-Way Association (AREMA) loading specifications of the rail-seat positive moment test.
Keywords: Transfer length; Prestressed concrete railroad ties; Civil Engineering (0543)